2012
DOI: 10.1002/jmri.23948
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MR imaging for differentiating between benign and malignant thyroid nodules: Initial experience in 23 patients

Abstract: The multiparametric MR imaging helps discriminating malignant thyroid nodules from benign ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The majority of the recent DCE-TIC studies of thyroid nodules showed that most malignant thyroid carcinomas displayed a plateau pattern, while most benign lesions showed a rapid washout pattern. [8][9][10] However, Gupta et al's results came to contradictory conclusions using different parameters including dynamic phases, injection rates, contrast dosages, and scan sequence. 11 Based on these contradictory conclusions, reasonable parameters in thyroid DCE-TIC studies still need to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the recent DCE-TIC studies of thyroid nodules showed that most malignant thyroid carcinomas displayed a plateau pattern, while most benign lesions showed a rapid washout pattern. [8][9][10] However, Gupta et al's results came to contradictory conclusions using different parameters including dynamic phases, injection rates, contrast dosages, and scan sequence. 11 Based on these contradictory conclusions, reasonable parameters in thyroid DCE-TIC studies still need to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…In their study the mean ADC values of PTC and contralateral normal thyroid tissue did not show any significant difference, but the mean ADC values of PTCs with extrathyroidal extension (ETE) were significantly lower than that of PTCs without ETE. The majority of the recent DCE‐TIC studies of thyroid nodules showed that most malignant thyroid carcinomas displayed a plateau pattern, while most benign lesions showed a rapid washout pattern . However, Gupta et al's results came to contradictory conclusions using different parameters including dynamic phases, injection rates, contrast dosages, and scan sequence .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate image segmentation is the premise of radiomics analyses. Most previous studies adopted a manual single-section (S-S) region of interest (ROI) analysis for the quantitative assessment of thyroid nodules to avoid necrotic, cystic and micro-calcified areas [6,7,[14][15][16][17], while few studies used whole-lesion (W-L) ROI analyses [12,[18][19][20]. Notably, the appropriate ROI size and positioning have considerable influence on the quantitative parameters of tumour and interobserver variability [21,22].…”
Section: Introductionmentioning
confidence: 99%